PUBLIC PARTICIPATION IN PREVENTION AND RESOLUTION OF DRUG PROBLEMS IN BANG PHLI YAI SUBDISTRICT ADMINISTRATIVE ORGANIZATION, BANG PHLI DISTRICT, SAMUT PRAKAN PROVINCE - Neenthammaroj, Thanyapat; Hombunma , Pannathorn (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims 1) to study the level of public participation in preventing and solving drug problems in Bang Phli Yai Subdistrict Administrative Organization, Bang Phli District, Samut Prakan Province. 2) To study the problem of public participation in preventing and solving drug problems in the area of Bang Phli Yai Subdistrict Administrative Organization, Bang Phli District, Samut Prakan Province, and 3) To study the guidelines for promoting public participation in preventing and solving drug problems in the area of Bang Phli Yai Subdistrict Administrative Organization, Bang Phli District, Samut Prakan Province. Samut Prakan is a mixed method research, starting with quantitative research and followed by qualitative research using documentary research and in-depth interviews with key informants, analyzing data and summarizing according. The research results found that; 1) The overall level of public participation in preventing and solving drug problems is at a moderate level. 2) The overall problems and obstacles to public participation in preventing and solving drug problems are at a high level. 3) Guidelines for promoting prevention and solving drug problems in the area of Bang Phli Yai Subdistrict Administrative Organization, Bang Phli District, Samut Prakan Province. When considering each aspect, it can be summarized as follows: (1) Guidelines for promoting participation in decision-making found that it should promote the recruitment of volunteers, recruit personnel to carry out activities to prevent and solve drug problems, support people in the community to participate in expressing their opinions to find gold together. (2) Guidelines for promoting participation in operations found that it should promote participation and support people in the area to cooperate with various agencies, monitor order, report clues of people involved in drugs and drug-related offenses, and campaign to provide knowledge to people in the area. (3) Guidelines for promoting participation in receiving benefits found that it should promote local people to cooperate in preventing and solving drug problems, promote people's quality of life, safety of life and property, and seriously enforce the law in implementing activities to prevent and solve drug problems in the area. (4) Guidelines for promoting participation in evaluation found that it should promote participation in expressing opinions, suggesting guidelines for preventing and solving drug problems, publicize the results of the activities, and continuously report the results of the activities. Support monitoring of the work of government officials. Local people should participate in inspecting the implementation of drug prevention and solving projects, including conducting satisfaction surveys on drug prevention and solving activities in the area.